Handgrip Strength and Its Associated Factors among Community-dwelling Elderly in Sri Lanka: A Cross-sectional Study - Damayanthi, Hewaratne Dassanayakege Wimala Thushari; Moy, Foong Ming; Abdullah, Khatijah Lim; Dharmaratne, Samath Dhamminda (Elsevier, 2018)
Purpose: Low muscle strength is central to geriatric physical disabilities and mortality. The purpose of the present study was to examine handgrip strength (HGS) and its associated factors among community-dwelling older people in Sri Lanka. Methods: A cross-sectional study was conducted in the Kandy district using multistage sampling. A total of 999 older people were recruited, with a female preponderance. Data were collected using interviewer-administered questionnaires on demographic characteristics, depression, and physical activity. Anthropometric measurements including weight, height, mid-upper arm circumference, calf circumference, and HGS were recorded. Complex sample general linear model was used to examine the association between HGS and its associated factors. Results: The mean highest HGS of the study group was 12.56 kg (95% confidence interval: 11.94–13.19). Male older people had a higher HGS (17.02, 95% confidence interval: 15.55–18.49 kg) than females (10.59, 95% confidence interval: 10.12–11.06 kg). For both men and women, older age was associated with lower HGS, while mid-upper arm circumference was associated with better HGS. Diabetes mellitus, vegetarian diet, and alcohol consumption were associated with HGS for women only. Conclusion: Men had a higher HGS compared with women. Age, mid-upper arm circumference, diabetes mellitus, vegetarian diet, and alcohol consumption were factors associated with HGS among community-dwelling older people in Kandy district, Sri Lanka. HGS can be used as a feasible strategy to improve health status of older people by community health nurses.